An Efficient Network-Wide Reliable Broadcast Protocol for Medical Sensor Networks - Wang, Xinguo; Hu, Run; Wang, Lutao; Gao, Dongrui; Su, Yuyuan; Yang, Bin (Industrial IoT Technologies and Applications, 2021)
Medical sensor networks provide rich contextual information and alerting mechanisms with continuous monitoring. Broadcast is an important communication mode for medical sensor networks. Most existing broadcast protocols for wireless sensor networks use a minimal virtual backbone subnetwork to broadcast packets, which can minimize the total number of transmissions. However, since the unreliability of wireless link is not considered, the broadcast efficiency of these protocols is not high in factual networks. This paper proposes an efficient networkwide reliable broadcast protocol (ENWRB), which adopts network coding scheme to reduce the retransmissions in single-hop broadcast and a link quality-aware virtual backbone election algorithm to generate the more efficient broadcast backbone. Simulation results show that, under the same premise of ensuring all nodes receive broadcast packets successfully, the efficiency of ENWRB is higher than that of Hierarchical CDS-based Algorithm (HCA) greatly.